Compatibility of wrist exoskeletons with human biomechanical and neural constraints - Mohammad Esmaeili Malekabadi (2015)
Daily motor tasks are often kinematically redundant as they involve more degrees-of-freedom (DoF), for example in the human limbs, than strictly required. Humans are known to adopt motor strategies which consist of a stereotypical selection of specific postures for a given task. Such natural strategies are also known to be perturbed when, for example, operating in contact with machines or robots. To this end, a wrist exoskeleton, specifically designed to minimally perturb motor strategies, was used to study the effects of ergonomic factors and mechanical impedance on human motor strategies during redundant tasks. The novelty of this work is in accounting for the neural constraints imposed by the brain during redundant tasks. Special attention is devoted to wrist robots since the human wrist, together with the hand, is involved in most manipulation tasks, from cooking to micro-surgery, from dart-throwing to calligraphy. To comply with kinematic constraints, ergonomic considerations are introduced at an early stage of structural design of passive exoskeleton, matching the biomechanical constraints imposed by human anatomy. Due to inter-subject anatomical differences, subject-specific kinematic models are determined through a non-invasive protocol. The kinematic models are used to design subject-specific exoskeletons. The effects of kinematic compatibility on motor strategies are assessed through numerical and experimental studies and solutions from literature are adapted to avoid over-constrained configurations. Finally, confirming that perceived inertia is responsible for the perturbation of natural motor strategies during redundant tasks, a low-inertia wrist exoskeleton with one active DoF is devised and tested to be compatible with both biomechanical and neural constraints during pointing tasks.